2019
DOI: 10.1055/a-0808-3834
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal duodenal (“windsock”) diverticulum: a rare cause of biliary obstruction and acute pancreatitis in the adult

Abstract: An intraluminal duodenal diverticulum (IDD) is a rare congenital anomaly, which is a result of incomplete recanalization of the foregut lumen during embryonic development. Most patients are asymptomatic. Symptoms usually occur after the third decade of life and mainly include epigastric pain, nausea, vomiting, or bloating. Less commonly, IDD may complicate with bleeding, duodenal obstruction, or acute pancreatitis. We present a case of IDD, manifested for a first time in adult with acute biliary obstruction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Endoscopic treatment is the preferable approach as a less invasive procedure without major adverse effects. Endoscopic techniques include simple needle-knife incision (diverticulotomy), partial snare resection (diverticulectomy), endoscopic retrograde cholangiopancreatography (ERCP), and sphincterotomy with balloon dilation [7][8][9][10][11]. Furthermore, a new endoscopic technique for diverticulectomy has been exploited with impressive results including a 2-channel endoscope [10] and an expandable metallic stent inserted into the diverticulum [11].…”
Section: Biliopancreatic Manifestationmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic treatment is the preferable approach as a less invasive procedure without major adverse effects. Endoscopic techniques include simple needle-knife incision (diverticulotomy), partial snare resection (diverticulectomy), endoscopic retrograde cholangiopancreatography (ERCP), and sphincterotomy with balloon dilation [7][8][9][10][11]. Furthermore, a new endoscopic technique for diverticulectomy has been exploited with impressive results including a 2-channel endoscope [10] and an expandable metallic stent inserted into the diverticulum [11].…”
Section: Biliopancreatic Manifestationmentioning
confidence: 99%
“…Nowadays, with advancements in endoscopy and imaging; endoscopic diverticulotomy or diverticulectomy is the treatment of choice. The endoscopy approach includes using needle-knife papillotomy, sphincterotomy, argon plasma coagulation, yttrium aluminum garnet (YAG) laser, and endostapler have been described [7][8][9][10][11][12][13][14][15][16][17]. In a study by Bhalla et al, the use of a novel technique reported as submucosal dissection scissors (SB knife, (Olympus, Shinjuku City, Tokyo, Japan)) and blended the longitudinal wall by electrocautery showed resolution of symptoms [14].…”
Section: Obstructionmentioning
confidence: 99%
“…The clinical manifestations of duodenal duplications may be asymptomatic or symptomatic and depend on the stage of development and size. When a duplication is enlarged, bleeding, perforated, or obstructed, patients may experience recurrent episodes of pain, hemorrhage, and pancreatitis (3)(4)(5). To diagnose, a duodenal duplication is very challenging because there are no specific characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of duodenal diverticula is estimated at 22% of the population in autopsy [2,3], with only 5% of those presenting symptoms [3] and only 1-2% of patients requiring surgery [4]. Duodenal diverticula can demonstrate a wide spectrum of symptoms due to compression of the surrounding organs, cholestasis, haemorrhage, inflammation or perforation [3,[5][6][7][8][9][10][11][12]. Perforation is an extremely rare complication and until 2013 only 162 cases were described in the literature [3,13].…”
Section: Introductionmentioning
confidence: 99%